Karakterisasi Fisis Dan Mekanis Interface Zone Dari Laser Coatings Cu-Ni-Fe-Si-B Dan Ni-Cr-B-Si - Perpustakaan UGM, i-lib ([Yogyakarta] : Department of Chemistry Gadjah Mada University, 2000)
Interface zone properties of Cu-Ni-Fe-Si-B and Ni-Cr-B-Si laser coatings have been investigated by Vickers and Hertzian microindentation method, whereby a hard pyramid or spherical indenter is pressed into the solid specimen surface. By measuring elastic and elastoplastic depth of indenter penetration, can be determined the hardness, elastic modulus and yielding stress of interface zone of the specimen. These devices have very high sensitivity, which allow an investigation of the mechanical properties of surface layers as small as several micrometers thickness. These methods were applied to estimate the hardness, elastic modulus and yielding stress of laser coatings with 0,1 mm to 1,0 mm thickness